2017
DOI: 10.1159/000477258
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Adhesion Assessment as a Predictor for Pneumothorax after Endobronchial Valve Treatment

Abstract: Background: Pneumothorax after bronchoscopic lung volume reduction using one-way endobronchial valves (EBVs) in patients with advanced emphysema occurs in approximately 20% of patients. It is not well known which factors predict the development of pneumothorax. Objective: To assess whether pleural adhesions on pretreatment high-resolution computed tomography (HRCT) scans are associated with pneumothorax occurrence after EBV treatment. Methods: HRCT scan analyses were performed on all patients who received EBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…These efforts could also result in more insight to predict patients who are at risk of a pneumothorax after treatment. Currently, the predictors of the risk of a pneumothorax are not clear and studies reported even contradictory results [28,29].…”
Section: Burning Questionsmentioning
confidence: 99%
“…These efforts could also result in more insight to predict patients who are at risk of a pneumothorax after treatment. Currently, the predictors of the risk of a pneumothorax are not clear and studies reported even contradictory results [28,29].…”
Section: Burning Questionsmentioning
confidence: 99%
“…pleurodesis or pleurectomy) are most often excluded for endobronchial valve treatment [22]. Adhesions may be visible on CT-scan, but currently it is not known whether this correlates to treatment success or the ability to achieve an atelectasis [23]. If there is no effect after treatment with valves, there is no presence of collateral ventilation and revision bronchoscopy did not show evidence of valve dysfunction, adhesions may be the cause of the treatment failure.…”
Section: Adhesionsmentioning
confidence: 99%
“…33 Improved patient selection has significantly improved patient outcomes but it is also evident that the main adverse event as a result of inducing lobar atelectasis or volume reduction is a secondary pneumothorax. 19,34,35 This is presumably due to the remodelling that occurs with volume loss, further decreasing pleural pressures and any areas where the lung is adherent to the pleura may lead to a tear and cause a pneumothorax. This risk ranges from 20% to 25% in the clinical trials and is reflective in clinical practice.…”
Section: Zephyr Ebvmentioning
confidence: 99%